Digital Banking Optimization Strategy for Gold Investment as an Alternative Long-Term Investment - Oktaningrum, Indarti Indah; Mardani, Ronny Malavia; Nurhidayah, Nurhidayah (Electronic Journal of Education, Social Economics and Technology, 2025)
The digital transformation taking place in the financial sector not only affects people's transaction patterns, but also expands access to various investment instruments. One instrument that shows significant convergence in the digital era is gold. Gold, as a traditional asset with safe haven characteristics, is now increasingly accessible through digital banking platforms provided by banks, including Bank Syariah Indonesia. This study aims to explore digital banking optimization strategies towards gold investment opportunities as an alternative long-term investment in Bank Syariah Indonesia. The approach used is exploratory qualitative, with data collection techniques through in-depth interviews and documentation studies. Data analysis was conducted using the SWOT approach and strategy formulation through the TOWS matrix. The findings show that although the digital gold investment feature is available on most of Bank Syariah Indonesia's platforms, the utilization rate is still relatively low. The contributing factors include lack of customer education, lack of integration of investment analytics features, and unoptimized user interface design. Suggested strategies include improving educational features, developing a risk profile-based investment recommendation system, and strategic collaboration between banks and sharia-based fintech platforms. This research is expected to provide theoretical contributions in the development of digital financial services strategies as well as practical contributions for the banking industry in increasing digital-based investment inclusion.